PURPLE LEAVES (Graptophyllum pictum L. Griff) AND PINEAPPLE (Ananas comosus L. Merr.) FOR THE PRODUCTION OF HERBAL TEA TO SUPPORT NERVOUS SYSTEM HEALTH - Aritonang, Hosianna Stephany; Makkiyah, Feda Anisah (The SDGS Forum Communication, 2025)
This study explores the potential of purple leaves and pineapple as raw materials for producing herbal tea. It examines the availability of these plants in Indonesia, analyzes their bioactive compounds, investigates the tea production process, and evaluates food safety through toxicity and microbiological testing. The research employs an experimental approach, integrating literature reviews, phytochemical analysis, and laboratory testing. The study involves identifying key bioactive compounds in purple leaves and pineapple, formulating an optimal tea blend, and conducting toxicity and microbial safety evaluations.The study finds that purple leaves contains flavonoids, alkaloids, and tannins, which possess neuroprotective and anti-inflammatory. Pineapple contains bromelain and vitamin C, which are known for their antioxidative and anti-inflammatory. This research provides a novel contribution by introducing a herbal tea formulation combining purple leaves and pineapple. It offers valuable insights into the potential of Indonesian herbal resources for functional food development and phytopharmacology.